Impairment of Intermediate Filament Expression Reveals Impact on Cell Functions Independent from Keratinocyte Transformation - Charlotte Klein; Imke Ramminger; Shuoqiu Bai; Thorsten Steinberg; Pascal Tomakidi (Cells)
Although cytoplasmic intermediate filaments (cIFs) are essential for cell physiology, the molecular and cell functional consequences of cIF disturbances are poorly understood. Identifying defaults in cell function-controlled tissue homeostasis and understanding the interrelationship between specific cIFs and distinct cell functions remain key challenges. Using an RNAi-based mechanistic approach, we connected the impairment of cell-inherent cIFs with molecular and cell functional consequences, such as proliferation and differentiation. To investigate cIF disruption consequences in the oral epithelium, different cell transformation stages, originating from alcohol-treated oral gingival keratinocytes, were used. We found that impairment of keratin (KRT) KRT5, KRT14 and vimentin (VIM) affects proliferation and differentiation, and modulates the chromatin status. Furthermore, cIF impairment reduces the expression of nuclear integrity participant lamin B1 and the terminal keratinocyte differentiation marker involucrin (IVL). Conversely, impairment of IVL reduces cIF expression levels, functionally suggesting a regulatory interaction between cIFs and IVL. The findings demonstrate that the impairment of cIFs leads to imbalances in proliferation and differentiation, both of which are essential for tissue homeostasis. Thus, targeted impairment of cIFs appears promising to investigate the functional role of cIFs on cell-dependent tissue physiology at the molecular level and identifies putative interactions of cIFs with epithelial differentiation.